Who or what has agency in the discussion of antimicrobial resistance in UK news media (2010-2015)?: a transitivity analysis - Collins, Luke Curtis; Jaspal, Rusi; Nerlich, Brigitte (Sage, 2017)
The increase of infections resistant to existing antimicrobial medicines has become a topic of concern for health professionals, policy makers and publics across the globe, however among the public there is a sense that this is an issue beyond their control. Research has shown that the news media can have a significant role to play in the public’s understanding of science and medicine. In this article, we respond to a call by research councils in the UK to study antibiotic or antimicrobial resistance as a social phenomenon by providing a linguistic analysis of reporting on this issue in the UK press. We combine transitivity analysis with a Social Representations framework in order to determine who and what the social actors are in discussions of antimicrobial resistance (AMR) in the UK press (2010-2015), as well as which of those social actors are characterised as having agency in the processes around AMR. Findings show that antibiotics and the infections they are designed to treat are instilled with agency; that there is a tension between allocating responsibility to either doctors-as-prescribers or patients-as-users; and collectivisation of the general public as an unspecified ‘we’: marginalising live-stock farming and pharmaceutical industry responsibilities.